Optimization Of Livestock Data Management With The Implementation Of Naïve Bayes In The Agricultural Service Information System At The Tomohon City Agriculture Office - Mario Rettob Rettob; Vivi Piggie Rantung (Politeknik Ganesha Medan, 2023)
Case Study Research: Optimization of Livestock Data Management with the Implementation of Naïve Bayes in the Information System of the Department of Agriculture in Tomohon City. according to the data this year there was a lot of increase in the livestock sector, especially cattle, which was caused by the high birth rate this year, coupled with data stating that the growth of cattle in the Tomohon area was rapid but under control, with a lot of demand and also the number of births, making the Department want to predict the number of births and the success of cows for the upcoming watku. with the hope that the prediction process produced by the Naive Bayes algorithm is expected to make it easier for the Department to get results that can become predictive data for the future. With the hope that the prediction process produced by the Naive Bayes algorithm is expected to make it easier for the Department to get results that can become predictive data for the future. The study of prediction is one way to know the impact of the development that occurs in cattle in a period of time that can be determined so that a handling plan can be made if there is a spike and cannot be controlled, it can also control the birth rate and production of cows in Tomohon.Changes and predictions that can be made by utilizing existing livestock data can be done using a data analysis program with input data on cow development, cow care and cow gender. The simulation results can show the prediction of birth and also the success of cows